Effective fabric store system for efficient fabric shopping - Sanjonco, John Leonard G.; Rayala, Ma. Monica E. (Quezon City College of Home Economics, University of the Philippines, 2014)
ABSTRACT This is a descriptive study which focused on effective fabric store systems for efficient fabric shopping. Based on three (3) elements used in a retail system ? product/merchandise, store layout, customer service, interviews with fabric store personnel and observations were done in three (3) selected fabric stores in Metro Manila to describe the existing fabric store system. Three (3) fabric retail stores and thirty (30) fabric store customers were purposively selected to participate in the study. Data was analyzed through simple statistical tools. The results of the study indicated that the existing fabric store system answers some of the needs and concerns of the customers such as having a wide variety of fabrics to choose from, and having enough space inside the store for customers to walk around and check all of the merchandise available. However, there is a need to improve in some other areas, such as having proper and up-to-date fabric name and price labels so that it will be easier for the customers to identify the fabrics they need. Improvement in the store product display was also found necessary. A well organized display according to type or function and colors of the fabrics is helpful for the customers and store personnel because they would not have to go around the store anymore just to find the fabrics they need. The study also found that there is a need to improve the current assistance system practiced by the fabric stores as it is time consuming not only on the part of the customers but on the part of the store personnel as well.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Stores, Retail -- Philippines